Lung Cancer Deaths Among American Indians and Alaska Natives, 1990–2009 - Plescia, Marcus (American Public Health Association, 2014)
Objectives. We examined regional differences in lung cancer among American Indians/Alaska Natives (AI/ANs) using linked data sets to minimize racial misclassification. Methods. On the basis of federal lung cancer incidence data for 1999 to 2009 and deaths for 1990 to 2009 linked with Indian Health Service (IHS) registration records, we calculated age-adjusted incidence and death rates for non-Hispanic AI/AN and White persons by IHS region, focusing on Contract Health Service Delivery Area (CHSDA) counties. We correlated death rates with cigarette smoking prevalence and calculated mortality-to-incidence ratios. Results. Lung cancer death rates among AI/AN persons in CHSDA counties varied across IHS regions, from 94.0 per 100 000 in the Northern Plains to 15.2 in the Southwest, reflecting the strong correlation between smoking and lung cancer. For every 100 lung cancers diagnosed, there were 6 more deaths among AI/AN persons than among White persons. Lung cancer death rates began to decline in 1997 among AI/AN men and are still increasing among AI/AN women. Conclusions. Comparison of regional lung cancer death rates between AI/AN and White populations indicates disparities in tobacco control and prevention interventions. Efforts should be made to ensure that AI/AN persons receive equal benefit from current and emerging lung cancer prevention and control interventions.